Pembangunan Talent Management System yang Terintegrasi dengan SAP Netweaver (Studi Kasus: PT Kereta Api Indonesia) - Aditya Bayu Wardhana; Denny Sagita Rusdianto; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT KAI already has a system that can assess the performance of their employees, it is called Performance Management System. However the system still has not been able to overcome the existing problems. These problems, the difficulty in retain the best people in the company and also difficulties in the recruitment of new high quality employee. This is caused by the increasing competition of intercompany and limited supplies of the talent. So we need system which can overcome these problems, that is Talent Management System. PT KAI has an application that supports Talent Management process, that is SAP Netweaver. PT KAI has not applied it to such SAP application. This is due to different business processes and requires high cost to do further development on the SAP Netweaver application. Developing Talent Management System requires several methods, including the BSC, 360 Degree Assessment, and MBTI. As well as the required way to integrating data between Talent Management System with SAP Netweaver application, that is by using SAP RFC. This system has been successfully tested using white box testing technique for unit and integration testings, and black box testing technique for validation testing.